Psychological, physical and sexual violence against brazilian women: a cross-section study - Gustavo Correia Basto da Silva; Osires de Medeiros Melo Neto; Robson Kel Batista de Lima; Natália Medeiros Andrade; Ricardo Alves de Olinda; Alessandro Leite Cavalcanti (Acta Scientiarum. Health Sciences, 2023)
The objective was to characterize the notifications of urban violence against women, according to psychological, physical and sexual typologies. This is a cross-sectional, documentary, descriptive and analytical research, based on the notification forms of the Brazilian Notifiable Diseases Information System between the years 2014 and 2017, referring to a city in the Northeast. The independent variables were divided according to the most prevalent types of violence, while the dependent ones followed the characteristics suggested by the notification forms. The data were analyzed using the Chi-square and Fisher's Exact tests, with a significance level of 5%, in addition to calculating the Chance Ratio. RStudio was used as statistical software.447 notification forms were included, with the following prevalences being observed: psychological (80.1%), physical (39.2%), and sexual (21%), with a predominance of women with low educational level (<8 years of study), non-white race, without companions and heterosexuals. Most of the notifications pointed to the repetition of violence, occurring mainly at night, in homes and public roads, in the form of threats, and the use of body strength. Women are exposed to psychological, physical, and sexual violence, especially to the psychological form, possibly because they have a pattern intrinsically associated with other types.